Cultural Aspects on Subtitling Videos from Bahasa Indonesia Into English - Ismailia, Titik (Politeknik Negeri Jember, 2019)
Translation activity is the way to translate one language into another language. In this process some aspects may involved. One of them is cultural aspect. Christiane (2001) said that culture is dynamic qualities on human action and behavior including language in a society. While Newmark (1988) said that culture is the way of life and manifestation of peculiar community that uses a particular language in expressions. Furthermore, Newmark categorization on cultural aspects includes ecology (flora, fauna, winds, plains, hills), material culture (artefacts, food, clothes, houses and towns, transport), social culture (work and leisure), organizations, customs, activities, procedures, concepts (political and administrative, religious, artistics ), gestures and habits. Based on those definitions and categories, the writer analyze student’s assignment on translations course. It consisted of 5 videos with folklore theme. The result shows that all those categories found. It shows that every language has its own cultural aspects and translation can give new knowledge to the writer and students as well. Keywords:cultural aspects, subtitling videos from bhs Indonesia into English,